Improvement of Technology of Automation of Cement Packing Process At "Eco Sement" Enterprise (Texas Journal of Engineering and Technology, 2023)
in "ECO CEMENT" enterprise cement packaging process automation technology new work analysis to do Smart packaging the device offer to do Cement packing process importance analytical and of the device work analysis to do